Therapeutic Plasma Exchange in Crisis Myasthenia Gravis with Pregnancy - Anak Agung Ayu Lydia Prawita; Ida Ayu Putri Wirawati; Sianny Herawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Myasthenic Crisis (MC) is a clinical diagnosis defined by respiratory failure in patients with Myasthenia Gravis (MG). As MG symptoms worsen, the weakness of the respiratory muscles or upper airway can increase so much that it causes difficulty swallowing or breathing, resulting in respiratory distress. One of the triggers for a myasthenic crisis is pregnancy. In this case, the patient was undergoing a second pregnancy with a gestational age of 28-29 weeks and had been diagnosed with MG 4 years ago. The female patient, 27 years old, had complaints of shortness of breath, difficulty chewing, and weakness in the extremities. During her stay in the hospital, the patient's condition worsened and she experienced a myasthenic crisis. Therapeutic Plasma Exchange (TPE) was administered to the patient 3 times and the patient's had clinical improvement. The patient was discharged with pyridostigmine and methylprednisolone therapy. Therapeutic plasma exchange is a safe and effective procedure for the management of myasthenia gravis during pregnancy. Prompt diagnosis and proper management can reduce morbidity in myasthenia gravis, especially those in crisis.